Brand Storytelling on Social Media: Connecting with Consumers in the Digital Age - Parab, Anisha (ATLAS SkillTech University, 2025)
The internship report "Brand Storytelling on Social Media: Connecting with Consumers in the Digital Age" gives a broad overview of my enriching experience as an Account management Intern at Gozoop Pvt. Ltd.-leading digital marketing agency. Under the mentorship of my Director and seniors, I was able to work my way through a complex, dynamic environment of a fast-growing agency, connecting the gap between theoretical concepts and real-life business challenges. The following report gives an elaboration on the importance of such hands-on experience as contributing to professional growth and aligning academic knowledge with the modern demands of doing business. The following summary tries to give a peek into the minute details of findings and reflections put across in further sections of this report, which will help the readers understand the worth of this transformational internship experience at Gozoop Pvt Ltd.
Project Report on Brand Storytelling on Social Media: Connecting with Consumers in the Digital Age (2023-2025) Under the Guidance of Prof. Kajal Chheda
Keywords: Digital Age; Digital Marketing; Marketing; Management